Mobile Health Tool to Capture Social Determinants of Health and Their Impact on HIV Treatment Outcomes Among People Who Use Drugs: Pilot Feasibility Study - Rachel E Gicquelais; Caitlin Conway; Olivia Vjorn; Andrew Genz; Gregory Kirk; Ryan Westergaard (JMIR Formative Research)
Abstract BackgroundActive substance use, food or housing insecurity, and criminal legal system involvement can disrupt HIV care for people living with HIV and opioid use disorder (OUD). These social determinants of health are not routinely captured in clinical settings. ObjectiveWe evaluated whether real-time reports of social and behavioral factors using a smartphone app could predict viral nonsuppression and missed care visits to inform future mobile health interventions. MethodsWe enrolled 59 participants from the AIDS Linked to the Intravenous Experience (ALIVE) Study in Baltimore, Maryland, into a 12-month substudy between February 2017 and October 2018. Participants were eligible if they had OUD and had either a measured HIV RNA ≥1000 copies/mL or a ≥1-month lapse in antiretroviral therapy in the preceding 2 years. Participants received a smartphone and reported HIV medication adherence, drug use or injection, and several disruptive life events, including not having a place to sleep at night, skipping a meal due to lack of income, being stopped by police, being arrested, or experiencing violence on a weekly basis, through a survey on a mobile health app. We described weekly survey completion and investigated which factors were associated with viral nonsuppression (HIV RNA ≥200 copies/mL) or a missed care visit using logistic regression with generalized estimating equations adjusted for age, gender, smartphone comfort, and drug use. ResultsParticipants were predominantly male (36/59, 61%), Black (53/59, 90%), and had a median of 53 years old. At baseline, 16% (6/38) were virally unsuppressed. Participants completed an average of 23.3 (SD 16.3) total surveys and reported missing a dose of antiretroviral therapy, using or injecting drugs, or experiencing any disruptive life events on an average of 13.1 (SD 9.8) weekly surveys over 1 year. Reporting use of any drugs (adjusted odds ratio [aOR] 2.3, 95% CI 1.4‐3.7), injecting drugs (aOR 2.3, 95% CI 1.3‐3.9), and noncompletion of all surveys (aOR 1.6, 95% CI 1.1‐2.2) were associated with missing a scheduled care visit over the subsequent 30 days. Missing ≥2 antiretroviral medication doses within 1 week was associated with HIV viral nonsuppression (aOR 3.7, 95% CI: 1.2‐11.1) in the subsequent 30 days. ConclusionsMobile health apps can capture risk factors that predict viral nonsuppression and missed care visits among people living with HIV who have OUD. Using mobile health tools to detect sociobehavioral factors that occur prior to treatment disengagement may facilitate early intervention by health care teams.